An ultra-wideband (UWB) rectangular dielectric resonator antenna (DRA) / Abdullah Farid Mansor - Mansor, Abdullah Farid (2017)
The design of an Ultra-Wideband (UWB) Rectangular Dielectric Resonator Antenna (DRA) is presented in this paper. There are three main objectives of this project. The first objective is to achieve the best performance of Ultra-Wideband (UWB) system. The second objective is to design the compact size of antenna with improvement of bandwidth and the last objective is performance analysis of antenna. The proposed antenna was analysed and designed using CST Microwave Studio software. The simulated results show the with 10-dB reference which it can operate at 3 .1 GHz until 8.33 GHz. The ultra-wideband (UWB) communication system operate from 3.1 GHz until 10.6 GHz. The bandwidth of an Ultra-Wideband (UWB) Rectangular Dielectric Resonator Antenna (DRA) was 5.233 which cover 70% of ultra-wideband (UWB) applications. An Ultra-Wideband (UWB) Rectangular Dielectric Resonator Antenna (DRA) was build up with the compact size of antenna which 40 x 40 mm. Furthermore, the antenna has been analysed and discussed. The performance analysis of the return loss, the radiation pattern, the input impedance and the gain were presented.